(untitled) (Comparative & International Education Series, 2022)
It had long been a dream of mine to study abroad, specifically, in Canada because of the world-renowned education system and diverse culture. When the opportunity of studying in Canada came to me, I had an ambivalent feeling: thrilled and concerned. I was overjoyed because my childhood dream was finally about to come true. However, I hesitated to move abroad because of the uncertainty surrounding my future. I had to leave my stable teaching job and my family and friends. After careful consideration, I decided to move to Vancouver to obtain my master’s degree in Education. After I started my studies in Vancouver, I encountered many unexpected and challenging situations related to my daily and professional life. Among them, a couple of events impacted my life significantly.